Application of advanced electrovectorcardiographic methods in the diagnosis of left ventricular hypertrophy on the basis of Uryupinsk central district hospital - Vishnyakova N.A.; Ryabykina G.V.; Sakhnova T.A. (Системные гипертензии, 2016)
The aim of the study was to evaluate the possibilities of left ventricular hypertrophy (LVH) detection with the use of a complex including a system of remote 12-lead electrocardiography (ECG) analysis, orthogonal lead ECG and vectorcardiography (VCG), during the medical examination of the population of Uryupinsk district of the Volgograd region. The work was organized in two rural district hospitals of Uryupinsk district. 180 persons were randomly selected out of the total data bank. Of these, according to ECG and VCG, 54 persons (30%) were considered to be practically healthy, and in 63 cases (35%) automatical analisys of ECG or VCG revealed signs of LVH. In 32 cases (50.7%) left ventricular hypertrophy was revealed for the first time. The most often finding was the increase of the parameters of synthesized orthogonal ECG and VCG: the sum of Rx+Sz and maximal QRS vector (89%, 95%). About 10% of the patients had high blood pressure without electrocardiographic signs of LVH. Introduction of the remote ECG analisys to the work of medical institutions of Uryupinsk district allowed to increase LVH detection.